Collaborative tools in higher education: the use of Wikis by industrial and mechanical engineering students - Gaspar, Marcelo (2017)
Continuous technological advances keep challenging current and future engineers to anticipate and adapt to the new trends and paradigms that are expected to take place in a near future. One of such paradigms is the Industry 4.0 that encompasses the promise of a new industrial revolution based on the interconnectivity of people and systems to communicate, analyse and use information related to industrial processes. New challenges, as well as new opportunities, will rise in this digital landscape, demanding from future engineers the ability to adapt and grow in such ground-breaking environments. With such dynamic changes taking place in the current and future industries, engineering education has to adapt and prepare future graduates to work and function in these demanding environments. The set of skills envisaged to be held by future engineers is the ability to work and collaborate using digital means of participation as well as the ability to effectively use intercultural communicative skills. To this end, an exploratory study was conducted among different European Higher Education Engineering Schools to integrate a project with common aims and goals, resulting in various collaborative engineering activities that were designed to be carried out by undergraduate industrial and mechanical engineering students to further improve their learning outcomes and to acquire, or improve on, dedicated intercultural, communicative and colaborative skills. Following both quantitative and qualitative approaches, this study combined different types of data and methods of analysis in order to provide an exploratory account of the envisaged findings.